A review on hydrothermal carbonization of biomass and plastic wastes to energy products. (March 2020) - Shen, Yafei
Abstract: Hydrothermal carbonization (HTC) as a promising thermochemical process can convert organic solid wastes (e.g., biomass, plastics) into valuable products (i.e., hydrochar) at relatively low temperatures (180–250 °C) and saturated pressures (2–10 MPa). Hydrothermal conversion generally occurs via dehydration, polymerization and finally carbonization reactions. The carbon materials derived from hydrochar have high potential in various applications such as solid fuel, supercapacitor, fuel cell, and sorbent. Although the energy densification of hydrochar was increased at higher temperatures, most of the benefit was achieved at modest temperatures. Chemical structures of hydrochars include crosslinks of aromatic polymer, surface porosity, organic functional groups and ultimate components. All of these characteristics can be changed significantly by HTC, influencing the reactivity and fuel properties of hydrochars. The reaction pathways including negative and positive effects during (co)-HTC of biomass and plastic wastes are thoroughly concluded. In particular, the co-HTC of chlorinated plastic (e.g., PVC) and biomass can enhance the dechlorination and inorganics removal from hydrochar. Graphical abstract: Image 1 Highlights: Hydrothermal carbonization of biomass and plastic wastes was reviewed. Hydrochar with high energy density can be used as a coal-alternative solid fuel. Hydrochar can be chemically activated into porous carbons for energy storage. HTC is mostly influenced by the feedstock types and processing conditions. Co-HTC of plastics and biomass can improve the quality of hydrochar.